Heat transfer characteristics of urea-water spray impingement on hot surfaces. (February 2018) - Liao, Yujun; Dimopoulos Eggenschwiler, Panayotis; Furrer, Roman; Wang, Moyu; Boulouchos, Konstantinos
Highlights: Experimental study of urea-water spray impingement under hot flow conditions. The wall temperature fundamentally determines the spray/wall heat transfer. 3D inverse heat conduction problem solved to estimate spray cooling heat fluxes. Different boiling regimes identified for urea-water spray impingement. Critical heat flux and Leidenfrost points shifted to higher temperatures. Abstract: This study presents an investigation of the heat transfer characteristics of the urea-water spray (UWS) impingement on a stainless steel plate under typical diesel exhaust flow conditions. The rear side temperature of the spray-impinged plate has been measured by infrared thermography with high temporal and spatial resolution. The spray impinged side temperature and heat flux distributions have been computed by solving the 3D inverse heat conduction in the plate with the sequential function specification method. Measurements show that the instantaneous plate temperature determines the heat transferred during the spray impingement. Based on the plate temperature, different regimes (film boiling, transition boiling and nucleate boiling) have been identified. At high plate temperatures, film boiling and Leidenfrost effect are prevailing and the heat transferred from the plate to the liquid is low. With decreasing plate temperatures, the critical heat flux regime is approached and the heat transferred increases substantially. At lower plate temperatures, nucleate boiling occurs limiting the heat transferred to low values. The critical heat flux and temperature found for UWS are reported and in good agreement with the trend in previous studies for water.